SYNERGISTIC CORROSION-WEAR EFFECT IN AUSTENITIC POWDER METALLURGICAL STEEL WITH DIFFERENT TITANIUM ADDITIONS (2022)
To ascertain the influence of titanium percentage in 316L austenitic steel, titanium percentages varied from 0.5 to 2% aggregated to 316L steel. The powder metallurgy method was used. The powdered material was pressed at 800 MPa and then sintered at 1300°C. The X-ray diffraction (XRD) technique was used to characterize the identification of the phases after the processed mixtures. Wear and tribowear properties were determined by pin on disc tests. Electrochemical polarization curves were used to study corrosion. According to the results of the samples, the corrosion resistance of titanium increased to a percentage of 1.5% due to the formation of the phases generated by the mixture. However, it was determined that the most appropriate percentage is 2%, due to the synergistic mode specifically for wear and corrosion resistance, the mechanism is the most adequate.